Learning the isolation of bioactive compounds and the utilization of the seven winds plant (polygala paniculata l) as an anti-mosquito innovation of aedes aegypti l - Suharno Zen; Widya Sartika Sulistiani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to explore the isolation of bioactive compounds from Polygala paniculata L. (Seven Winds plant) and evaluate its potential as an environmentally friendly anti-mosquito innovation. The research employed a laboratory-based experimental approach, including precise steps for sample preparation, extraction, partitioning, and phytochemical testing. A total of 500 grams of Polygala paniculata plant material were used, sourced from rice field areas where the plant naturally grows. The plants were washed, air-dried in the shade, and ground into simplicia. The simplicia was extracted using the maceration method with methanol for 24 hours, repeated four times. The extract was then evaporated using a rotary evaporator at 40–45°C, yielding 28.72 grams of viscous extract. The extract was partitioned using n-hexane and ethyl acetate solvents to separate compounds based on their polarity. Phytochemical analysis identified several bioactive compounds, including alkaloids, flavonoids, tannins, saponins, terpenoids, and phenolics. Among these, flavonoids, saponins, and terpenoids were identified as having significant potential biological activity, including natural insecticide properties. Although direct testing on Aedes aegypti was not conducted, the findings suggest that these compounds could play a role in future mosquito control applications. The study also contributes to educational practice by enhancing students’ understanding of bioactive compound isolation techniques. This study provides an example of how local biodiversity can be explored to develop eco-friendly solutions, with the potential for natural mosquito repellent products in the future. Further studies are needed to test the toxicity of these compounds and their practical efficacy in field conditions.